2018
DOI: 10.1007/s11916-018-0682-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endothelin in the Pathophysiology of Migraine—a Systematic Review

Abstract: We identified 23 articles. Nine studies reported on endothelin-1 plasma concentrations in patients with migraine, eight studies investigated relevant genetic associations, five studies investigated endothelin-1 and spreading depression in animals, and one randomized controlled clinical trial tested the efficacy of an endothelin antagonist in the acute treatment of migraine in patients both with and without aura. Elevated endothelin-1 plasma levels have been reported in the early phase of migraine attacks. Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 84 publications
0
30
1
Order By: Relevance
“…A role for ET‐1 in the pathophysiology of migraine has been suggested, primarily based on observations of increased plasma ET‐1 levels in the early phase of migraine attacks with and without aura, studies reporting abnormalities of the ET‐1 and ETA receptor genes in migraine patients, and studies of CSD‐induction in animals using ET‐1 . While the biochemical and genetics studies suggest an involvement of ET‐1 in migraine in general, they do not clearly support involvement of ET‐1 specifically in migraine with aura .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for ET‐1 in the pathophysiology of migraine has been suggested, primarily based on observations of increased plasma ET‐1 levels in the early phase of migraine attacks with and without aura, studies reporting abnormalities of the ET‐1 and ETA receptor genes in migraine patients, and studies of CSD‐induction in animals using ET‐1 . While the biochemical and genetics studies suggest an involvement of ET‐1 in migraine in general, they do not clearly support involvement of ET‐1 specifically in migraine with aura .…”
Section: Discussionmentioning
confidence: 99%
“…Migraine aura is a well‐known complication of sclerotherapy for varicose veins and plasma ET‐1 levels are increased in patients following this procedure . A recent, large genome‐wide association study found that migraine is associated with a gene variant that causes the higher expression of the ET‐1 gene and increased binding of ET‐1 to ETA receptors on vascular smooth muscle cells . Collectively, these observations suggest that ET‐1 may trigger CSD, and thus migraine aura symptoms, in patients suffering from migraine with aura.…”
Section: Introductionmentioning
confidence: 98%
“…7,8 ET-I antagonists have been studied unsuccessfully in migraine. 9 While it has been suggested that ET-I could be a primary factor in the attack-triggering cascade of migraine with and without aura 6 based on the findings of the present study, the authors state "it seems clear that even very high acute increases in systemic ET-1 levels (exceeding those seen in, eg, acute myocardial infarction) do not affect CBF or oxygen metabolism." Very elevated ET-I levels also do not affect migraine with aura, nor produce more headache than placebo.…”
Section: Comments: This Cooperation Primarily Between the Glostrup Dementioning
confidence: 54%
“…3,4 ET-I potently induces spreading depression in animals, 5 possibly explaining the connection between endothelial irritation and migraine aura. 6 Some migraine persons are reported to harbor ET receptor A gene variants which modulate migraine risk. 7,8 ET-I antagonists have been studied unsuccessfully in migraine.…”
Section: Comments: This Cooperation Primarily Between the Glostrup Dementioning
confidence: 99%
See 1 more Smart Citation